Estimating Time-Varying Beta of Price Limits and Its Applications in China Stock Market - Rongquan Bai; Zuoquan Zhang; Menggang Li (Journal of Applied Mathematics)
This paper proposes an estimation method of time-varying beta of price limits. It uses China stock market trading data to estimate time-varying beta and researches on systemic risk in China stock market. By comparing prediction errors of market model, SS market model, and Censored-SS market model, it verifies the effectiveness of Censored-SS market model. Furthermore it has some meaningful conclusions in China stock market.